2022
DOI: 10.1021/acsomega.1c06983
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Thermally Stable Semiaromatic Polyamides by Bulk Polymerization Using Aromatic Diamines and Aliphatic Dicarboxylic Acids

Abstract: Semiaromatic polyamides were directly synthesized by bulk polycondensation of aliphatic dicarboxylic acids (with 5, 6, 7, and 10 carbon numbers) and aromatic diamines (4,4′-oxydianiline and 4,4′-diaminodiphenylmethane) under natural pressure. In addition, copolyamides were successfully obtained by the copolymerization of aliphatic dicarboxylic acids, aromatic diamines, and biobased amino acid, 4-aminohydrocinnamic acid. The obtained polyamides had relatively high inherent viscosity values of 0.35−0.76 dL/g. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…SSP does not require organic solvents or stoichiometric coupling agents and is performed industrially for the chain extension of polyesters, polycarbonates, and polyamides . However, there are only a few reports describing the use of SSP to synthesize SAPs from semi-aromatic amino acids. , Preliminary experiments with various additives revealed that hypophosphite (H 2 PO 2 – ) facilitated the SSP of AMF (Table S2). Specifically, sodium hypophosphite (NaH 2 PO 2 ) was identified as an effective promoter of SSP that caused the least amount of discoloration in the polymer product (Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…SSP does not require organic solvents or stoichiometric coupling agents and is performed industrially for the chain extension of polyesters, polycarbonates, and polyamides . However, there are only a few reports describing the use of SSP to synthesize SAPs from semi-aromatic amino acids. , Preliminary experiments with various additives revealed that hypophosphite (H 2 PO 2 – ) facilitated the SSP of AMF (Table S2). Specifically, sodium hypophosphite (NaH 2 PO 2 ) was identified as an effective promoter of SSP that caused the least amount of discoloration in the polymer product (Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, shorter‐chain monomers usually depict a greater degree of intramolecular cyclization during step‐growth polymerization. [ 39 ] Accordingly, M1 was reacted efficiently with DT4 in 1.0 M dichloromethane (DCM) at ambient temperature (a.t.) overnight (ON) in the presence of 0.3 wt.% DMPA to yield polymer P4 , which was isolated with an apparent number average molecular mass ( M n ) of 40 200 g mol −1 (with dispersity, Ð , of 2.0 as determined by size exclusion chromatography (SEC) relative to polymethylmethacrylate (PMMA) standards in tetrahydrofuran (THF) as eluent). Complementary to SEC, 1 H‐NMR spectroscopy of P4 unambiguously confirmed the formation of the targeted poly(thioether) decorated with two 1,5‐tetrazole units in each repeating unit and revealed a very high monomer conversion as judged from the decreased signal intensity of olefinic protons at 5.7 and 4.9 ppm (Figure S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, high dispersity values are rather typical for polymer chains having a relatively high tendency of cyclization. [40] The latter is particularly taking place during the step-growth polymerization of any short alkyl chain length derivatives, such as DT1. In point of fact, Kricheldorf, [41] in many of his works, has emphasized that decreasing the alkene length in any reactive bifunctional monomer is inducing the cyclization tendency of the system (defined as the ratio of rate constants of cyclization vs. chain extension).…”
Section: Polymer Dithiol a )mentioning
confidence: 99%
“…The major obstacles in the use of aromatic polyamides are their limited solubility in common organic solvents and the high heat resistance that makes their processing difficult [ 8 , 9 ]. Many studies have shown strategies to improve the processability of polyamides via the structural design of new monomers [ 8 , 9 , 10 , 11 ]. Aromatic diamine is one of the major building blocks to tailor the properties of the synthesized polyamides [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%